Nasce il G-Mett dell’Università di Tor Vergata - Ioannilli, Maria (GEOmedia, 2008)
The University of Tor Vergata G-Mett Lab University of Tor Vergata's (Rome) civil engineering department presents its land methodologies and technologies laboratory, also called G-Mett. The laboratory promotes the integration of the different instances that usually take part in the land-urban planning and management.